PERKEMBANGAN CORPORATE SOCIAL RESPONSIBILITY DI INDONESIA - Tanudjaja, Bing Bedjo (Institute of Research and Community Outreach - Petra Christian University, 2006)
The awareness towards CSR (Corporate Social Responsibility), that should be integrated into a company's hierarchy as management's strategy and policy, is needed to attain balance between the business industry and the surrounding community. The essence and significance of CSR has not been wholly understood by businessmen, thus CSR only becomes textual and often implemented due to community demand. Abstract in Bahasa Indonesia: Kesadaran terhadap CSR (Corporate Social Responsibility) yang seharusnya telah terintegrasi dalam hierarki perusahaan sebagai strategi dan policy manejemen, diperlukan demi tercapainya sebuah keseimbangan dunia usaha antara pelaku dan masyarakat sekitar. Esensi dan signifikansi dari CSR masih belum dapat terbaca sepenuhnya oleh pelaku bisnis, sehingga CSR sendiri bagi sebagian pelaku bisnis baru sekedar wacana dan terkadang implementasinya berdasarkan atas tuntutan masyarakat. Kata kunci : corporate social responsibility, pelaku bisnis, masyarakat.